2021
DOI: 10.3390/atmos12020127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Pedestrian Thermal Comfort on Water-Retaining Pavement for UHI Adaptation Strategy

Abstract: Artificial impervious surfaces are one of the most significant factors contributing to urban heat islands (UHIs). Adapting to UHIs is a challenge in achieving thermal comfort. We conducted a quantitative and subjective evaluation of a closely paved novel water-retaining pavement (WR) and a conventional dense-asphalt pavement (AS). We investigated the thermal states of humans based on the human energy balance known as “human thermal load” as an indicator for the assessment, and the original human thermal load m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Covering with elements of the urbanized environment is one of the indicators of the intensity of development, showing a close relationship with the surface temperatures [ 289 , 290 ]. Impermeable surfaces in the neighborhood unit represented by buildings and roads have constant high LST and UHI [ 161 , 172 ], and modulation of the coverage parameter strongly influences their variability [ 291 , 292 , 293 , 294 ]. The increase of paved surface coverage leads to LST and UHI increases [ 295 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Covering with elements of the urbanized environment is one of the indicators of the intensity of development, showing a close relationship with the surface temperatures [ 289 , 290 ]. Impermeable surfaces in the neighborhood unit represented by buildings and roads have constant high LST and UHI [ 161 , 172 ], and modulation of the coverage parameter strongly influences their variability [ 291 , 292 , 293 , 294 ]. The increase of paved surface coverage leads to LST and UHI increases [ 295 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…Increasing the built-up area coverage by 1% may cause a rise of the UHI effect intensity up to 1.7% [ 170 ]. On the other hand, a 1% reduction may cause a decrease in the night-time near-surface air temperature by 0.1 °C [ 292 ]. Urbanization degree is proportional to the distance from the city center [ 187 ] and size-dependent urban area [ 172 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…These characteristics help to decrease the surface temperature, reducing the convection of heat from the pavement to the atmosphere and thereby decreasing the air temperature. Previous studies have demonstrated that an increased albedo by 0.1 is estimated to reduce the maximum pavement surface temperature by more than 3.0 • C [20,21]. Lower air temperatures contribute in mitigating the UHI effect [22], while also decreasing the energy demand for cooling, and slowing the formation of urban pollution [23].…”
Section: Reflective Pavementsmentioning
confidence: 99%
“…However, the porous structure will also reduce the pavement reflectivity and weaken the cooling effect [73,92]. Water retaining pavement can absorb water during raining or watering, and prolong the time with water [93][94][95]. In addition, water-retaining materials are generally in light color, which can improve the reflectivity of the pavement to a certain extent, thereby improving the cooling effect [92].…”
Section: Evaporative Coolingmentioning
confidence: 99%